ChemInform Abstract: 3‐Aryl‐6‐methoxy‐2‐oxo‐1, 2‐dihydroquinoline‐4‐carbonitriles (VII) as Solvent and pH Independent Green Fluorescent Dyes. Issue 19 (18th April 2013) - Enoua, Guy Crepin; Uray, Georg; Stadlbauer, Wolfgang
Abstract synthesis and electronic spectra